FRI0482-HPR Clinical tools association in knee osteoarthritis patients. Objective measures vs subjective measures. (23rd January 2014) - Martin-Martin, L.; Magro-Checa, C.; Valenza, C.; Castellote-Caballero, Y.; Caracuel-Martinez, J.C.; Fajardo-Rodriguez, M.; Valenza, G.
Abstract : Background: Knee osteoarthritis (OA) is the most common disease of joints in older adults around the world. It is a chronic condition associated with pain and reduction in physical function, leading to a negative impact on the physical and psychosocial well-being of patients. Therefore, different instruments have been developed to evaluate the impact of OA on functioning and quality of life of patients 2 Objectives: To determine the association between subjective and objectivemeasuring tools of knee osteoarthritis patients enrolled in Spanish primary care Methods: 120 patients with radiologically confirmed knee osteoarthritis. The following scores were calculated and recorded for logistic regression analysis: Visual Analogue Scale (VAS) for pain, Western Ontario and McMaster Osteoarthritis Index (WOMAC) for functional status, and EQ-5D for Health related quality of life, radiographic severity measured by Kellgren-Lawrence grade (K/L), age and Body Mass Index (BMI) Results: An 80% of the sample were women, mean (SD) age 64, 11 (10, 361) and BMI 31, 40 kg/m 2 (5, 3). Radiographic severity mean (SD) was 2, 63 (0, 685) and 75% had more affected joints besides knee. Mean (SD) standardized tools scores were: EVA 6, 46 (2, 3 SD); EQ-5D 0, 58 (0, 23); EQ-5D VAS 56, 6 (16, 9); WOMAC pain 8, 97 (3, 7); WOMAC stiffness 3 (2); WOMAC function 29, 5 (12, 8) and WOMAC global 41, 5 (16, 86). No significant association between radiographic severity and subjective health statewas finding. Age and BMI were not correlated either, although older people had worse radiologic severity (p=0, 002), and fattest people had more pain and stiffness measured by WOMAC index Conclusions: This sample shows that radiographic severity does not match with knee symptomatology as other studies have previously assert. Just WOMAC index was correlated with objective measures. Further studies could inquire why higher BMI is associated with worse stiffness and pain scores in WOMAC index but does not impact in people function References: Tsonga T, Kapetanakis S, Papadopoulos C, Papathanasiou J, Mourgias N, Georgiou N Open Orthop J Xie F, Pullenayegum EM, Li SC, Hopkins R, Thumboo J, Lo NN Value Health Disclosure of Interest: None Declared